Cloning and expression study of a high-affinity nitrate transporter gene from Zea mays L. (31st December 2023) - Li, Guoliang; Chang, Xu; Dong, Yi; Wang, Mingquan; Yang, Jianfei; Hu, Guanghui; Shumei, Jin
ABSTRACT: A nitrate transporter gene, named B46NRT2.1, from salt-tolerant Zea mays L. B46 has been cloned. B46NRT2.1 contained the same domain belonging to the major facilitator superfamily (PLN00028). The results of the phylogenetic tree indicated that B46NRT2.1 exhibits sequence similarity and the closest relationship with those known nitrate transporters of the NRT2 family. Through RT-qPCR, we found that the expression of B46NRT2.1 mainly happens in the root and leaf. Moreover, the treatment with NaCl, Na2 CO3, and NaHCO3 could significantly increase the expression of B46NRT2.1 . B46NRT2.1 was located in the plasma membrane. Through the study of yeast and plant salt response brought by B46NRT2.1 overexpression, we have preliminary knowledge that the expression of B46NRT2.1 makes yeast and plants respond to salt shock. There are 10 different kinds of cis-acting regulatory elements (CRES) in the promotor sequences of B46NRT2.1 gene using the PlantCARE web server to analyze. It mainly includes hormone response, abscisic acid, salicylic acid, gibberellin, methyl jasmonate, and auxin. The B46NRT2.1 gene's co-expression network showed that it was co-expressed with a number of other genes in several biological pathways, including regulation of NO3 long-distance transit, modulation of nitrate sensing and metabolism, nitrate assimilation, and transduction of Jasmonic acid-independent wound signal. The results of this work should serve as a good scientific foundation for further research on the functions of the NRT2 gene family in plants (inbred line B46), and this research adds to our understanding of the molecular mechanisms under salt tolerance.